Biofilm of Salmonella Typhimurium on polypropylene : effect of cinnamaldehyde and proteomic analysis - Silva, Alex Fiori da (2015)
Salmonella spp. is the most important foodborne pathogen, leading to consequences, especially to public health and food industry. The effect of cinnamaldehyde against Salmonella enterica serotype Typhimurium ATCC 14028 planktonic and biofilm cells on polypropylene was evaluated. Additionally, differential protein pattern expressed by planktonic and biofilm bacteria, as well protein expression on biofilms treated with cinnamaldehyde, was also evaluated. Minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of cinnamaldehyde were 312 and 624 μg/mL, respectively. Time-kill curve assay demonstrated that cinnamaldehyde presented bacteriostatic activity at sub-MIC and MIC concentrations and completely eliminated bacterial cells at 624 μg/mL after 12 h of exposure. S. Typhimurium formed biofilm on polypropylene, observed by colony counts (8.03 log CFU/cm2) and scanning electron microscopy. Cinnamaldehyde at 234 μg/mL (0.75 x MIC) decreased 1.3 log CFU/cm2 during 48 h of biofilm formation, while treatment for 1 h with cinnamaldehyde at 624 μg/mL reduced 2.33 log CFU/cm2 of 2-days-old biofilm. In proteomic analysis of biofilm compared to planktonic cells, 16 proteins were up and 5 were down-regulated. Lipoprotein Lpp, 30S ribosomal protein S2 and 50S ribosomal protein L3 were indentified only in biofilm cells, suggesting their importance on biofilm formation. In cinnamaldehyde-treated biofilm, it was identified 8 up and 11 down-regulated proteins. Among down-regulated, serine hydroxymethyltransferase presented the major decrease (23.8-fold). Cinnamaldehyde showed antimicrobial activity against planktonic cells, nevertheless it was not effective to completely eliminate the biofilm on polypropylene. Proteomic analysis showed that biofilm cells presented differentially expressed proteins compared to its planktonic counterparts, especially proteins involved in cell metabolism. Moreover, it was also observed that proteomic profile of biofilm-treated cells is affect by cinnamaldehyde.